Analisis Metode Penjadwalan pada Proyek Bangunan Gedung: Studi Kasus Metode Line of Balance dan Precedence Diagram - Arifuddin, Rosmariani; Fatimah, Andi Nurul; Fadlillah, Muh Rifan (MEDIA KOMUNIKASI TEKNIK SIPIL, 2024)
The construction industry plays a significant role in a country's economic growth. However, construction projects frequently face challenges in meeting schedule targets. Project scheduling is crucial as it provides insights into enhancing the development process. Various scheduling methods are employed in construction projects, including the line of balance (LoB) method and precedence diagramming. Selecting the appropriate scheduling method impacts the project's timeline. This research aims to analyze the effectiveness of the LoB method and precedence diagramming in building construction projects, with a specific case study of a COVID center. The research method involves collecting project data, including project s-curves. The findings indicate that utilizing both the line of balance and precedence diagram methods can enhance project scheduling by ensuring the continuous allocation of resources.